Precursor type affecting surface properties and catalytic activity of sulfated zirconia - Zarubica Aleksandra R.; Bošković Goran C. (Acta Periodica Technologica, 2007)
Zirconium-hydroxide precursor samples are synthesized from Zr-hydroxide, Zr-nitrate, and Zr-alkoxide, by precipitation/impregnation, as well as by a modified sol-gel method. Precursor samples are further sulphated for the intended SO4 2- content of 4 wt.%, and calcined at 500-700oC. Differences in precursors’ origin and calcination temperature induce the incorporation of SO4 2- groups into ZrO2 matrices by various mechanisms. As a result, different amounts of residual sulphates are coupled with other structural, as well as surface properties, resulting in various catalytic activities of sulphated zirconia samples. Catalyst activity and selectivity are a complex synergistic function of tetragonal phase fraction, sulphates contents, textural and surface characteristics. Superior activity of SZ of alkoxide origin can be explained by a beneficial effect of meso-pores owing to a better accommodation of coke deposits.